Iron status of exclusively breastfed low-birth-weight infants born to anemic mothers and effect of maternal iron supplementation for 3 versus 6 months: A randomized double-blind placebo control trial - Fatima, Tarannum; Faridi, Mohammad Moonis Akbar; Srivastava, Geetika (Frontiers in Pediatrics, 2022)
Background: Effect of maternal iron supplementation during lactation on iron status of exclusively breastfed LBW infants is not known. Primary Objective: 1. To find out number of LBW exclusively breastfed infants having hemoglobin <10.5g/dl at 6 months when mothers received iron. 2. To find out proportion of anemic infants when mothers received iron for 3 months and 6 months. Design: CTRI registered trial (CTRI/2018/08/015516) Double-blind Randomized Control Trial Participants: Eighty anemic mothers and exclusively breastfed LBW infants. Intervention: Eighty anemic mothers and exclusively breastfed infants, birth weight 1500-2499gm, randomized into two groups of 40 each. Mothers received daily iron for 3 months and placebo for next 3 months in group A and iron for 6 months in group B. Iron profile of mothers and infants measured at recruitment and 6 months. Results: 26.6% infants developed anemia till 6 months of age and number of anemic infants were similar whether mothers received iron for 3 months (n=9) or 6 months (n=11). Hemoglobin (12.89+0.46 g/dl vs. 12.44+0.48 g/dl; p<0.001) and serum ferritin (27.45 +7.60 ng/ml vs. 18.94+5.36 ng/ml; p<0.001) were significantly higher in infants at 6 months of age whose mothers received iron for 6 months in comparison to 3 months. Conclusion: 26.6% exclusively breastfed infants developed anemia till 6 months of age when mothers took iron; number of anemic infants were not different if mothers received iron for 3 months or 6 months. Significant increase was noted in serum ferritin with slightly higher hemoglobin of infants when mothers received iron for longer duration.